Development of High Efficient Co3o4/Bi2o3/Rgo Nanocomposite for an Effective Photocatalytic Degradation of Pharmaceutical Molecules with Improved Interfacial Charge Transfer - Singh, D (Elsevier Ltd, 2022)
In this study, novel 3D/3D/2D-Co3O4/Bi2O3/rGO ternary nanocomposites is were successfully synthesized via hydrothermal technique assisted with self-assembly process. The prepared materials were characterized for their morphological, structural, and optical properties using various techniques such as XRD, FTIR, SEM, EDX, TEM, and UV-DRS. The compositions of 3D-Co3O4 and 3D-Bi2O3 in the ternary nanostructure were adjusted during the synthesis process to obtain a highly photoactive nanocomposite. The photocatalytic degradation ability of the ternary nanocomposite was significantly increased due to the Z-scheme photoexcited charge transfer process in the nanocomposite. The 2D rGO nanosheets in the ternary nanocomposite decreased the recombination of photoexcited charge carriers which increased the photocatalytic degradation efficiency of the nanocomposite. The photocatalytic degradation activity of 3D/3D/2D-Co3O4/Bi2O3/rGO ternary nanocomposite was studied for the degradation of tetracycline (TC) and ibuprofen (IBP) under visible light irradiation. Results showed that the Co3O4/Bi2O3/rGO ternary nanocomposite is a highly active catalyst for the degradation of TC and IBP. Trapping experiments were performed to scrutinize the predominant reactive species involved during photocatalytic degradation reactions. The ternary nanocomposite was successfully reused for five degradation cycles without remarkable loss in its catalytic activity. © 2022 Elsevier Ltd